Light‐Induced Degradation in Annealed and Electron Irradiated Silicon. Issue 17 (7th July 2019) - Lauer, Kevin; Krischok, Stefan; Klein, Thomas; Bähr, Mario; Lawerenz, Alexander; Röder, Ralf; Ortlepp, Thomas; Gohs, Uwe
Abstract : The composition of the defect, which is responsible for the boron–oxygen‐related light‐induced degradation (BO‐LID) of the carrier lifetime in silicon, still remains an unresolved issue. It has been recently suggested that the BO‐LID is due to the A Si ‐Si i ‐defect. Within this idea, the creation and discreation are governed by the interstitial silicon concentration. Annealing and electron beam (EB) irradiation are applied to influence the interstitial silicon concentration. The BO‐LID is observed in the case of diffusion‐oxygenated FZ (DOFZ) boron‐doped silicon after annealing at 650 and 450 °C for 4 h, respectively. A nearly complete discreation of the BO‐LID defect is found for the long‐term high temperature (16 h at 1050 °C) anneal. This discreation process is explained by the diffusion of the interstitial silicon atoms to other sinks such as the wafer surfaces. The degradation of the carrier lifetime due to illumination after the EB irradiation is unambiguously related to the BO‐LID phenomenon. Abstract : The composition of the boron–oxygen‐related light‐induced degradation (BO‐LID) defect is an unresolved issue. Recently, BO‐LID is suggested to be due to the A Si ‐Si i ‐defect. Thus, creation and discreation of BO‐LID is governed by the interstitial silicon concentration. Annealing and electron beam irradiation are applied. BO‐LID is created in oxygenated silicon after 4 h annealing at 650 °C and discreated by 16 h annealing at 1050 °C.